Analisis Hukum Perbandingan terhadap Pemberian Nafkah Anak Pasca Perceraian di Amerika Serikat dan Indonesia - Mariska Zena Wilona; Siti Masruroh; Syifa Afelyna Suryoputri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Divorce has significant implications for child welfare, particularly regarding post-divorce child support. In Indonesia, the effectiveness of fulfilling child support remains low because it relies on the obligor’s goodwill and lacks a centralized monitoring mechanism. This study compares child support regulations and factors influencing their effectiveness in Indonesia and the United States. Findings indicate that the United States implements a structured system through Child Support Enforcement (CSE), supported by a central administrative agency and legal enforcement mechanisms, including automatic income withholding. In Indonesia, specific regulations and a dedicated supervisory institution are not yet available, resulting in suboptimal enforcement of child support orders.